Sofia Coppola : the politics of visual pleasure - Backman Rogers, Anna (Berghahn Books, 2019)
"All too often, the movies of Sofia Coppola have been dismissed as "all style, no substance." But such an easy caricature, as this engaging and accessible survey of Coppola's oeuvre demonstrates, fundamentally misconstrues what are rich, ambiguous, meaningful films. Drawing on insights from feminist philosophy and psychology, the author here takes an original approach to Coppola, exploring vital themes from the subversion of patriarchy in The Virgin Suicides to the "female gothic" in The Beguiled. As Rogers shows, far from endorsing a facile and depoliticized postfeminism, Coppola's films instead deploy beguilement, mood, and pleasure in the service of a robustly feminist philosophy."